Measurement of the Zγ→νν‾γ production cross section in pp collisions at s=8 TeV and limits on anomalous ZZγ and Zγγ trilinear gauge boson couplings - V. Khachatryan; A.M. Sirunyan; A. Tumasyan (Physics Letters B, 2016)
An inclusive measurement of the Zγ→νν‾γ production cross section in pp collisions at s=8TeV is presented, using data corresponding to an integrated luminosity of 19.6 fb−1 collected with the CMS detector at the LHC. This measurement is based on the observation of events with large missing energy and with a single photon with transverse momentum above 145GeV and absolute pseudorapidity in the range |η|<1.44. The measured Zγ→νν‾γ production cross section, 52.7±2.1 (stat)±6.4 (syst)±1.4 (lumi) fb, agrees well with the standard model prediction of 50.0−2.2+2.4 fb. A study of the photon transverse momentum spectrum yields the most stringent limits to date on the anomalous ZZγ and Zγγ trilinear gauge boson couplings.